2022
DOI: 10.24036/pedagogi.v22i2.1336
|View full text |Cite
|
Sign up to set email alerts
|

Refleksi pembelajaran daring di perguruan tinggi: Survey atas mahasiswa di sembilan perguruan tinggi Indonesia

Abstract: Penelitian ini mengkaji kualitas penyelenggaraan pembelajaran online di perguruan tinggi dalam dua tahun terakhir. Data diperoleh dari mahasiswa dengan mengisi angket terbuka elektronik. Data tersebut kemudian dianalisis secara deskriptif-kualitatif dengan mengacu pada Critical Success Factors (CSFs). Penelitian ini menyoroti apa yang belum pernah ditemukan oleh peneliti lain. Pertama, kendala yang paling menonjol adalah rendahnya literasi digital dosen dan tingginya tingkat distraktor di lingkungan fisik maha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Research subjects in semester 3 to semester 7 of the Faculty of Education and Social Sciences, Nahdlatul Ulama University Blitar, 15 women, 15 men). The technical questionnaire for the effectiveness of online learning activities refers to subject indicators on student attitudes towards online learning (e-learning), motivation, trust in the internet (general internet self-efficacy), and commitments to online learning (Miftakhuddin et al, 2022). This technique is a step to find out student recognition of the effectiveness of online learning as an independent educational institution (Adriyanto et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…Research subjects in semester 3 to semester 7 of the Faculty of Education and Social Sciences, Nahdlatul Ulama University Blitar, 15 women, 15 men). The technical questionnaire for the effectiveness of online learning activities refers to subject indicators on student attitudes towards online learning (e-learning), motivation, trust in the internet (general internet self-efficacy), and commitments to online learning (Miftakhuddin et al, 2022). This technique is a step to find out student recognition of the effectiveness of online learning as an independent educational institution (Adriyanto et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…The decline in students' comprehension and academic skills also occurs at the senior secondary level and the equivalent (Hanafiah et al, 2022;Rajib & Puspita Sari, 2022;Salsabila et al, 2022;Saputra & Fernandes, 2023;Widyasari et al, 2022). Even more surprising, it seems that the level of tertiary education is not spared from the grip of the learning loss phenomenon (Assiddiqi & Soeryanto, 2021;Lismandasari & Farhan, 2022;Miftakhuddin et al, 2022;Permana et al, 2023;Satriani & Khoirul Anwar, 2023;Subandowo et al, 2021). Furthermore, it can be concluded that this alarming phenomenon occurs at all levels of education.…”
Section: Teaching and Learning During The Covid-19 Pandemicmentioning
confidence: 99%